Photocatalytic degradation of tetracycline under visible light using TiO2@sulfur doped carbon nitride nanocomposite synthesized via in-situ method. Issue 4 (August 2021) - Divakaran, Krishnan; Baishnisha, Amanulla; Balakumar, Vellaichamy; Perumal, Krishnan Nattamai; Meenakshi, Chandran; Kannan, Ramaraj Sayee
Abstract: This paper describes a TiO2 nanoparticles assembled sulfur-doped graphitic carbon nitride (SCN) nanocomposite synthesized via an in-situ method. The as-prepared materials were thoroughly characterized (XRD, FT-IR, XPS, UV-DRS, SEM and mapping analysis). The TiO2 @SCN nanocomposite exhibits higher photocatalytic activity towards tetracycline (TC) degradation under visible light compared to individual components. The TiO2 @SCN nanocomposite catalyst had good stability and reusability for five consecutive photocatalytic degradation experiments. These performances could be attributed to effective charge separation and less recombination of electron and hole pairs of TiO2 @SCN nanocomposite which was confirmed by higher photocurrent and lower impedance results. The role of catalysts weight, pH, and effect of TC concentration were optimized and discussed. Further, radical scavenger studies were clearly identified the elections and superoxide radicals act as the main role for the photo-degradation of TC. It is hoped that our work could offers to develop various nanocomposite for photocatalytic degradation of pharmaceutical pollutants and energy applications. Graphical Abstract: In this work, an efficient and cost-effective nanocomposite, TiO2 @sulfur doped carbon nitride nanocomposite synthesized via an in-situ method. The as-prepared TiO2 @SCN nanocomposite showed good photo degradation efficiency towards toxic tetracycline. ga1 Highlights: TiO2 @sulfur doped carbon nitride (SCN) nanocomposite were prepared by a simple in-situ method. The photocatalytic activity of TiO2 @SCN nanocomposite was evaluated by the degradation of tetracycline. The TiO2 @SCN nanocomposite shows improved electron - hole separation and less recombination rate. The TiO2 @SCN nanocomposite had good reproducible and stable for five repeated cycles.